2021
DOI: 10.1158/0008-5472.can-21-1499
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpolarized Carbon-13 MRI for Early Response Assessment of Neoadjuvant Chemotherapy in Breast Cancer Patients

Abstract: Hyperpolarized 13 C-magnetic resonance imaging (MRI) is an emerging tool for probing tissue metabolism by measuring 13 C-label exchange between intravenously injected hyperpolarized [1-13 C]pyruvate and endogenous tissue lactate. Here we demonstrate that hyperpolarized 13 C-MRI can be used to detect early response to neoadjuvant therapy in breast cancer. Seven patients underwent multiparametric 1 H-MRI and hyperpolarized 13 C-MRI before and 7-11 days after commencing treatment. An increase in the lactate-topyr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 51 publications
0
47
0
2
Order By: Relevance
“…The overexpression of MCT1 in grade 4 ccRCC in the TCGA-KIRC database strengthens this finding and, as MCT1 also predicts OS, it underlines its potential prognostic significance which is in agreement with existing literature [ 34 , 35 ]. Other biological factors may also control the formation of the labelled lactate, such as the expression of the enzyme LDH, the concentration of cofactor NADH/NAD + , as well as endogenous lactate levels [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overexpression of MCT1 in grade 4 ccRCC in the TCGA-KIRC database strengthens this finding and, as MCT1 also predicts OS, it underlines its potential prognostic significance which is in agreement with existing literature [ 34 , 35 ]. Other biological factors may also control the formation of the labelled lactate, such as the expression of the enzyme LDH, the concentration of cofactor NADH/NAD + , as well as endogenous lactate levels [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies of HP- 13 C-pyruvate MRI in many cancer models, including ccRCC, have shown treatment-induced metabolic changes as early as 24 h after the start of treatment [ 45 ]. Recent evidence from a clinical study has shown that early treatment response to neoadjuvant therapy can be assessed with HP- 13 C-pyruvate MRI after 7–11 days, which is associated with pathological complete response in patients with breast cancer [ 36 ]. Detecting successful treatment response earlier will play an increasingly important role in ccRCC with the advent of an increasing number of treatment options in advanced disease.…”
Section: Discussionmentioning
confidence: 99%
“…The ultimate aim is that every patient diagnosed with early-stage TNBC has a bespoke treatment pathway developed that fits their TNBC. The individualised use of preclinical models such as patient-derived organoids or xenografts ( 221 ), and the implementation of advanced radiodiagnostic techniques ( 222 ) are pivotal to achieving this goal. This type of integrated approach requires open and clear communication and collaboration between basic scientists, clinicians, and other scientific disciplines, for example, bioinformatics, mathematics, and physics, which will maximise the chance of success and ultimately enhance patient benefit.…”
Section: Discussionmentioning
confidence: 99%
“…The observable metabolites of [1- 13 C]pyruvate are lactate, bicarbonate, and alanine, providing information on key metabolic pathways within a single scan. As increased glucose uptake and lactate production in the presence of sufficient oxygen, known as the Warburg effect, is often observed in cancer, MRI with hyperpolarized [1- 13 C]pyruvate can aid prediction of aggression and therapy response [2,3]. Accordingly, in addition to studies in healthy individuals [4,5], cancer was the focus of the initial neuroimaging studies in disease [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%